Math, asked by twinkle50, 1 year ago

by using distributive property solve {9/16×4/12}+ {9/16×-3/9}

Answers

Answered by sijasubbiah
16
Hey

Here is your answer,

{9/16×4/12}+ {9/16×-3/9}

By using distributive property,

= 9/16 ( 4/12 - 3/9)
= 9/16 ( 1/3 - 1/3)
=9/16 (0)
= 0

Hope it helps you!
Answered by Mankuthemonkey01
10
Hey mate!!!!!

( \frac{9}{16} \times \frac{4}{12} ) + ( \frac{9}{16} \times \frac{ - 3}{9} )
taking 9/16 common

we have =
 \frac{9}{16} ( \frac{4}{12} + \frac{ - 3}{9} ) \\ = \frac{9}{16} ( \frac{4}{12} - \frac{3}{9} ) \\ = \times \frac{9}{16} ( \frac{12}{36} - \frac{12}{36} ) \\ = \frac{9}{16} ( \frac{0}{36} ) \\ = \frac{9}{16} \times 0 \\ = 0

0 \fbox\textbf{is your answer}

Hope it helps dear friend ☺️✌️✌️

twinkle50: it is really helpful
Mankuthemonkey01: Welcome
Similar questions